2021
DOI: 10.3390/su13137182
|View full text |Cite
|
Sign up to set email alerts
|

Implications for Sustainability of the Joint Application of Bioeconomy and Circular Economy: A Worldwide Trend Study

Abstract: The joint application of bioeconomy (BE) and circular economy (CE) promotes the sustainable use of natural resources, since by applying a systemic approach, it improves the efficiency of these resources and reduces the impact on the environment. Both strategies, which belong to the area of green economy, provide a global and integrated approach towards environmental sustainability, as regards the extraction of biological materials, the protection of biodiversity and even the primary function of food production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 105 publications
0
15
0
5
Order By: Relevance
“…In recent years, different organizations worldwide are investing in sustainable bioeconomy, which refers to the set of economic activities focused on obtaining products and services that generate economic value using biological resources as raw material, and that represents a more viable opportunity to direct current economies toward greater sustainability in the use of natural resources both in agriculture and industry, and in economic growth [21][22][23]. In this context, economies are being directed toward greater sustainability in the use of natural resources both in agriculture and industry, and for economic growth.…”
Section: Theoretical Framework: Circular Economy Applied To Agriculturementioning
confidence: 99%
“…In recent years, different organizations worldwide are investing in sustainable bioeconomy, which refers to the set of economic activities focused on obtaining products and services that generate economic value using biological resources as raw material, and that represents a more viable opportunity to direct current economies toward greater sustainability in the use of natural resources both in agriculture and industry, and in economic growth [21][22][23]. In this context, economies are being directed toward greater sustainability in the use of natural resources both in agriculture and industry, and for economic growth.…”
Section: Theoretical Framework: Circular Economy Applied To Agriculturementioning
confidence: 99%
“…Geographical distribution is not limited, while the date of publication is limited to the last 20 years. We chose the period of 20 years due to the facts given in previous research [15], where it is shown that our society has become more aware of the climate emergency that challenges the future of the planet in the last two decades. The literature search was conducted from February 2020 to February 2021 using the Scopus, Google Scholar, and Web of Science databases.…”
Section: State-of-the-art Review Methodologymentioning
confidence: 99%
“…The intention of the authors in carrying out this work is to focus on the field of sustainability. For this purpose, general parameters have been used, which are already used in a similar way in other works in which only terms derived from the root sustain* are used [62][63][64][65]. In addition, to include the perspective of the 2030 Agenda, terms drawn from the definition of the target on sustainable agriculture, contained in SDG 8, have been included.…”
Section: Methodsmentioning
confidence: 99%